Sudden changes in the amplitude‐frequency distribution of long‐period tremors at Aso volcano, southwest Japan. Issue 23 (11th December 2015) - Sandanbata, Osamu; Obara, Kazushige; Maeda, Takuto; Takagi, Ryota; Satake, Kenji
Abstract: We observed the activity of long‐period tremors (LPTs) with a period of 15 s at Aso volcano, Japan, during a 3 year period including the 2014 eruptions. The number of LPTs detected systematically increased 3 months before the Strombolian eruptions. LPT activity can be divided into five stages based on rapid changes in the maximum LPT amplitude. The amplitude‐frequency relation follows an exponential distribution during each stage before the Strombolian eruptions, with different characteristic amplitudes for each stage, indicating that the scale of the source property changed in stages. However, during a stage that persisted for 6 days after the onset of Strombolian activity, the amplitude‐frequency relation temporarily followed a power law distribution, indicating that the LPT source process no longer had a characteristic scale. In the last stage, the amplitude‐frequency relation returned to an exponential distribution. We therefore conclude that the physical source of volcanic LPTs changed during the eruption period. Key Points: Long‐period tremors at Aso volcano showed sudden changes during eruptions in 2014 The amplitude obeys an exponential distribution with different scale during most phases of eruptions Only just after Strombolian eruption start did the amplitude obey a power law distribution